IMPLEMENTASI KONSEP BALANCED SCORECARD DALAM MANAJEMEN SUMBER DAYA MANUSIA - Titik Nurbiyati (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2013)
Facing the competitive rivalry, many organization have implemented a tool to measure their performance. Organization have to measure the performance and contribution to the increase in the value of assets. Organizations not only measure financial performance but also non-financial. One of the competitive advantages of the organization is human resource. Consequently, there is increased emphasis on the importance of human resource performance measurement and determine how the contribution of human resources to organizational performance. Human Resources Scorecard (HR Scorecard) is a measurement system that links human resources with the company's strategy and performance will eventually be able to create awareness about the consequences of human resource investment decisions, so that the investment can be done in the right way and the right amount. Important element of the HR Scorecard is deliverable, use of High Performance Work Systems, HR Systems Alignment, HR Efficiency. The design phase of HR measurement system HR Scorecard approach as follows, 1) Identifying Competence HR Manager, 2) Measurement of High Performance Work Systems, 3) Measuring HR Alignment System, 4) resource efficiency, 5) HR Deliverables. One step implementation HR scorecard is a continuous monitoring and reporting of the target set strategic objectives are achieved. To the organizations, the measurement can be helpful in controlling the cost of value creation of the company, assess the contribution of HR to strategy implementation and support organizational change and flexibility. Keywords: Competitive advantage, performance measurement, HR, HR Scorecard